Efek Harga dan Kualitas Layanan terhadap Loyalitas Pelanggan di Dira Balung - Muhammad Wafi Hidayatullah; Pudhak Prasetiyorini; Febrina Gerhani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the partial and simultaneous effects of price and service quality on customer loyalty at Dira Balung, a family tourism destination located in Jember, Indonesia. The research is motivated by the growing competition in the tourism sector, where price perception and service quality are critical in shaping customer loyalty. A quantitative approach was employed, with data collected through structured questionnaires distributed to 94 respondents selected using purposive sampling. The data were analyzed using multiple linear regression to examine the relationships among the variables. The findings reveal that both price and service quality significantly influence customer loyalty, with service quality demonstrating a more dominant effect. Fair and reasonable pricing enhances customer trust and repeat visit intention, while service quality dimensions such as reliability, responsiveness, assurance, and empathy play a major role in sustaining customer satisfaction. Simultaneously, the interaction between price and service quality creates a synergistic effect that strengthens overall loyalty. The practical implications of this study emphasize the necessity for Dira Balung’s management to consistently integrate competitive pricing strategies with high-quality service standards to foster long-term customer relationships and ensure sustainable business growth. These results provide valuable insights for tourism managers in developing customer retention strategies in similar service-based industries.